2019
DOI: 10.7475/kjan.2019.31.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effect of Evidence-based Nursing Practice Guidelines for Pain Management in Patients with Dementia

Abstract: This study aimed to develop evidence-based nursing practice guidelines for pain management in patients with dementia and to verify their effects. Methods: Guidelines were developed according to the Clinical Practice Guideline Adaptation Manual. Additionally the quality of six guidelines was evaluated using the AGREE (Appraisal of Guidelines for Research & Evaluation) tool. Subsequently, the guidelines were translated into Korean and a preliminary set of guidelines was established. After a group of experts conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(2 reference statements)
0
3
0
1
Order By: Relevance
“…In a previous study of the elderly with dementia, behavioral psychological symptoms increased as the duration of dementia spread was longer and pain was present [11]. In addition, dementia patients who can communicate and dementia patients who have difficulty communicating should be distinguished, and pain behavior observation tools for dementia patients should be continuously used [12]. Elderly patients with dementia in geriatric care hospitals are different from the general elderly population in the community in terms of their abilities to express and assess pain.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of the elderly with dementia, behavioral psychological symptoms increased as the duration of dementia spread was longer and pain was present [11]. In addition, dementia patients who can communicate and dementia patients who have difficulty communicating should be distinguished, and pain behavior observation tools for dementia patients should be continuously used [12]. Elderly patients with dementia in geriatric care hospitals are different from the general elderly population in the community in terms of their abilities to express and assess pain.…”
Section: Discussionmentioning
confidence: 99%
“…This study is significant in that it verified self-rated health as a valid predictor of mortality using the national data of KLoSA, while considering the level of cognitive impairment for the first time. The level of pain, quality of life, and depression in cognitively impaired individuals had been continuously studied, and most studies on this topic have reported that the self-rated measures should be valued [ 12 , 15 , 17 , 18 ]. However, only a few studies have reported on the self-rated health of cognitively impaired individuals and none on the predictive power regarding mortality in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…However, the report of a caregiver may differ from the actual status of the cognitively impaired individual, and a growing emphasis has been placed on the self-assessment by cognitively impaired individuals [ 15 ]. In addition, there are studies supporting the reliability of self-assessment by cognitively impaired individuals regarding the quality of life or depression, unless communication is not possible or the level of cognitive impairment is severe [ 12 , 16 - 18 ]. Nonetheless, only a few studies have investigated whether self-rated health is a reliable indicator for cognitively impaired individuals, reporting inconsistent results [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of Phlebitis Rate between Two Groups 메신저 프로그램과 문자메시지를 이용하여 수시로 연락하여 상호 간의 의견을 교환하고, 정보를 공유함으로써 간호사들의 반응에 대처할 수 있도록 변화촉진자의 활동을 지원하 고 친밀감을 형성하였다. 이는 주 1회[23,24] 혹은 주 3회 이상[17] 변화촉진자와 면담[17,23,24]을 통해 주기적인 감사와 피드백을 수 대한 긍정적인 인식이 증가하여 나타난 결과로 생각된다. 근거기반실무에 대한 신념은 사전 3.27점으로 같은 도구를 사용 한 상급종합병원 간호사 3.45점[30], 3.38점[31]보다 낮은 수준이었 으나 사후에는 3.59점으로 상급종합병원 간호사보다 높은 수준으로 나는 내가 일하는 곳의 임상실무를 변화시키기 위해 근거기반 실 무지침이나 체계적 고찰을 이용하였다.…”
unclassified